The effect of emotional intelligence training on organizational citizenship behavior of primary teachers of Maku - nastaran dadashzadeh; akbar soleimannezhad; jafar ghahremani (پژوهش‌های روانشناختی در مدیریت)
Attention to organizational citizenship behavior is effective in improving employees’ performance and quality of services in organizations. Due to higher job pressure among employees, it seems like evaluating the effects of Emotional intelligence training on organizational citizenship behavior among employees is important. The project aims to study the effect of Emotional intelligence trainning on organizational citizenship behavior in elementary teachers.Research method was semi- experimental study with pre/post test and a control group design. Statistical population includes all female teachers of elementary teachers.The sampling process conducted with random method of stage cluster sampling.30 teachers were chosen as sample size and were assigned to experimental and control groups randomly. The research tools were Hoy and palo's OBC questionnaire and emotional intelligence training protocol. The validity and Reliabiliting of the questionnaire was acceptable. Descriptive statistical indexes and analysis of covariancetest were applied orderly to data description and testing of research hypotheses.The analysis results showed that the instruction of emotional intelligence has effect on organizational citizenship behavior and altruism, conscientiousness, courtesy, sportsmanship and civic virtue. instruction of emotional intelligence enhanced organizational citizenship behavior and altruism, conscientiousness, courtesy, sportsmanship and civic virtue.